Highly Efficient Catalytic Oxidation of Glucose to Formic Acid over Mn-Mo Doped Carbon Nanotube - Hongrui Guo; Fan Yang; Siwei Chen; Hejuan Wu; Jirui Yang; Feng Shen (Molecules)
The production of formic acid (FA) from lignocellulose and its derived sugars represents a pivotal upgrading reaction in biorefinery. This work prepared a Mn-Mo doped carbon nanotube composite catalyst for the catalytic oxidation of glucose into FA in an O2 atmosphere, under extremely low Mn (3.27%) and Mo (0.40%) loading conditions, displaying a comparable performance with the traditional vanadium-based catalyst suffering from toxicity issues. It was confirmed that the doping of Mo led to the formation of MnMoOX and increased the contents of low-valence Mn species (Mn2+ + Mn3+), lattice oxygen (Olatt), and surface adsorbed oxygen (Oads) based on various characterization methods, such as XRD, XPS, TEM and ICP, which were beneficial to improve the catalytic performance. The maximum FA yield of 58.8% could be achieved over Mn9Mo1OX@MWCNT after reaction for 6 h at 140 °C, which was far more than that obtained with undoped MnOX@MWCNT (14.5%) at the identical conditions. Glyoxylic acid and arabinose were identified as two main intermediates, suggesting that the transformation of glucose into FA over Mn9Mo1OX@MWCNT involved two different paths. This work proved that manganese-based catalyst was a green alternative for upgrading lignocellulose via catalytic oxidation.